Natural Deep Eutectic Solvent–Extracted Old and Young Mangrove Avicennia marina Leaves: Comparative Antibacterial Activity Against Propionibacterium acnes - Djamaludin, Heder; Firdaus, Shelina Innasa; Suprayitno, Eddy; Yahya, Yahya; Arisandi, Desy; Ahmad, Mirza Gulam; Tambunan, Jeny Ernawati; Ahmad, Nurul Hawa; Ramli, Nurul Shazini; Kartikaningsih, Hartati (Journal of Tropical Life Science, 2026)
Acne vulgaris is a common inflammatory skin disorder largely associated with the proliferation of Propionibacterium acnes. Although antibiotics are widely used for acne treatment, the increasing incidence of antibiotic resistance necessitates the exploration of effective natural alternatives. Mangrove plants are known to contain diverse bioactive compounds with antimicrobial potential. This study aimed to evaluate the antibacterial activity of Natural Deep Eutectic Solvent (NADES) extracts derived from young and old leaves of Avicennia marina against P. acnes. Extraction was conducted using citric acid–glucose-based NADES with different molar ratios: P1 (1:1), P2 (2:1), P3 (3:1), and P4 (4:1), to assess the effect of solvent composition on antibacterial performance. Antibacterial activity was determined using inhibition zone assays, while molecular docking analysis was performed to investigate interactions between extracted metabolites and P. acnes target proteins. The results showed that both young and old leaf extracts exhibited significant antibacterial activity, strongly influenced by the NADES formulation. Young leaf extracts produced the largest inhibition zone with the P4 formulation (24.51±0.75 mm) and the smallest with P1 (21.63±0.67 mm). Similarly, old leaf extracts showed maximum inhibition in P4 (37.38±4.34 mm) and minimum inhibition in P1 (22.62±1.40 mm). Increasing the proportion of citric acid enhanced the extraction of bioactive compounds responsible for antibacterial activity. Molecular docking confirmed strong binding affinities between key metabolites and P. acnes target proteins, supporting the experimental findings. Thus, NADES extracts of A. marina leaves, particularly those prepared using a 4:1 citric acid–glucose ratio, demonstrate strong potential as natural antibacterial agents for acne prevention and treatment.